Rollen und Einflussmöglichkeiten von Schreibzentren an deutschen Hochschulen. Ergebnisse einer deutschlandweiten Umfrage zu Rahmenbedingungen und Aktivitäten von Schreibzentren - Nora Hoffmann; Fridrun Freise (Hermes)
Although writing centers based on the US model are now widespread at German universities, they are still in the process of being established and institutionalized. This article (Roles and Possibilities of Influence of Writing Centers at German Universities. First Results of a Germany-wide Survey) explores the question of what role writing centers currently play at German universities after the expiry of the Quality Pact for Teaching, which facilitated their rise, and how they are institutionally positioned as actors. The article presents the initial results of a survey conducted in spring 2023 among writing centers at German universities, in which 77 of 146 existing centers participated. Data is presented on the institutional placement of the centers, the range of services offered, target groups, advice provided to university management, research activities, participation in internal decisions, and staffing. The aim of this article is to provide an empirically based stocktaking of the status of writing centers in Germany.